PTEN loss is associated with resistance to cetuximab in patients with head and neck squamous cell carcinoma. (April 2019) - Eze, Nnamdi; Lee, Ju-Whei; Yang, Dong-Hua; Zhu, Fang; Neumeister, Veronique; Sandoval-Schaefer, Teresa; Mehra, Ranee; Ridge, John A.; Forastiere, Arlene; Chung, Christine H.; Burtness, Barbara
Highlights: Immunofluorescence determined a PTEN cutpoint with 100% sensitivity and specificity. PTEN loss and PIK3Ca hotspot mutation were mutually exclusive. Cetuximab improved PFS in patients with PTEN expression/no PIK3Ca mutation (p = 0.0502). PTEN expression correlates with PFS for cetuximab-treated patients (HR = 0.35, p = 0.008). Abstract: Introduction: Cetuximab, a monoclonal antibody to the epidermal growth factor receptor (EGFR), extends survival in combination with standard therapy in head and neck squamous cell carcinoma (HNSCC). However, as effects are modest, and patients experience side effects, a biomarker to predict resistance and personalize therapy is needed. Activation of signaling pathways downstream from receptor tyrosine kinases predicts resistance to such therapies in other cancers. The most common abnormalities downstream from EGFR in HNSCC are in the PI3K pathway, activated via loss of expression of the regulator PTEN, or via PI3K mutation. We studied whether PTEN and/or PI3K abnormalities predict resistance to cetuximab. Methods: Tumor PTEN and PIK3CA /PI3K p110α were analyzed in samples from subjects treated on two trials of cetuximab-based therapy for patients with metastatic or recurrent HNSCC: E5397, a randomized trial of cisplatin plus placebo versus cisplatin plus cetuximab; and NCI-8070, a randomized trial of cetuximab plus sorafenib versus cetuximab. In situ quantification of PTEN and PI3K p110 α was performed using the AQUA™ method of quantitative immunofluorescence. PI3KCA hot spot mutations were determined with BEAMing. Results: For E5397, in multivariable analysis, PTEN expressing/ PIK3CA WT patients tended to improve PFS with cetuximab compared to placebo (N = 48; HR = 0.54, Wald p = 0.0502). High PTEN expression was significantly associated with superior PFS among patients treated on NCI-8070 (N = 37; HR = 0.35, p = 0.008). Conclusion: Loss of PTEN expression may be associated with lack of benefit from cetuximab. This analysis is limited by small sample size, and PTEN as a potential predictive biomarker merits validation in larger sample sets.